Hubungan Kebersihan Rongga Mulut Lansia Dengan Pengetahuan Pengasuh Lansia Tentang Perawatan Mulut Lansia Di Panti Werdha Trisno Mukti Turen - wibowo wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2020)
Background: Impaired physical mobility, communication and dementia can occur to anyone, but the risk increases with age which causes inability to perform daily activities as a result of reduced cognitive abilities including inability to maintain oral health. Elderly caregivers as people who daily interact to be the first line in performing oral care for the elderly have the same responsibilities in screening, planning oral care, oral hygiene, and access to dental care. Method: This study aims to analyze the relationship between oral hygiene of the elderly with the knowledge of elderly caregivers about the oral care of the elderly in the Nursing Home of Trisno Mukti Turen. The manipulation in this study were all elderly people who amounted to 37 and all elderly caregivers numbering 17 who were taken by purposive sampling technique. The measuring instrument used was the Oral Hygiene Index Simplified (OHIS) to measure the oral hygiene of the elderly and a questionnaire consisting of 10 questions to measure the knowledge of elderly caregivers. The analytical method used was to use ordinal logistic regression Results: There is a relationship between oral hygiene with the knowledge of elderly caregivers about oral care of the elderly. The Wald test value produced was 0.308 (p <0.05) which showed that there was a significant relationship between oral hygiene of the elderly (X1) to the knowledge of elderly caregivers about elderly oral care (Y). Conclusion: The problem of oral speech in the elderly is a problem that can occur in the elderly one of the causes of the problem is the lack of knowledge of the caregivers of the elderly about oral care of the elderly, thus increasing the knowledge of the caregivers of the elderly in this matter is the main thing that must be done.